Pengembangan Kompetensi Penyuluh Pertanian dalam Pendidikan Jarak Jauh Universitas Terbuka (UT): Kasus Alumni UT di wilayah Serang, Karawang, Cirebon dan Tanggamus - N. Huda; Sumardjo .; M. Slamet; P. Tjitropranoto (Institut Pertanian Bogor, 2009)
Agricultural extension agent must have several competencies in order to do their job properly. As educators, theyhave to master several competencies not only related to their personalities but also their professionalism,andragogic and social interaction abilities. This research was intended to formulate strategies for the developmentof agricultural extension agent competencies. Data were collected in July through December 2008. A surveytechnique was implemented among 111 agricultural extension agents who were graduated from UT in four differentlocations, namely Serang, Karawang, Cirebon and Tanggamus. Information from stakeholders were also collected toelaborate the findings. Data was analyzed by using descriptive and regression analysis. The findings indicated thatUT’s graduates tend to have a high level in competencies and have several dominant factors affecting theircompetencies.